2016
DOI: 10.1055/s-0036-1588024
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Physical Activity and Ginkgo Biloba on Cognitive Function and Oxidative Stress Modulation in Ischemic Rats

Abstract: Either exercise or Ginkgo biloba is reported to improve cognitive functioning. The aim of this study is to compare the protective effects of forced exercise and Ginkgo biloba on oxidative stress as well as memory impairments induced by transient cerebral ischemia. Adult male Wistar rats were treated with treadmill running or Ginkgo biloba extract for 2 weeks before cerebral ischemia. Memory was assessed using a Morris water maze (MWM) task. At the end of the behavioral testing, oxidative stress biomarkers were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
1
1
0
Order By: Relevance
“…On the contrary, GBE that has different beneficial ingredients for mental health showed amelioration in detrimental effect of chronic HH exposure on spatial memory. Similar observations were reported previously by Vaghef et al (2017) which illustrated protective effects of Ginkgo biloba L. on oxidative stress as well as memory impairments induced by transient cerebral ischemia. GBE has been reported to exhibit anti-inflammatory and neuroprotective properties in other studies ( Liang et al, 2018 ).…”
Section: Discussionsupporting
confidence: 92%
“…On the contrary, GBE that has different beneficial ingredients for mental health showed amelioration in detrimental effect of chronic HH exposure on spatial memory. Similar observations were reported previously by Vaghef et al (2017) which illustrated protective effects of Ginkgo biloba L. on oxidative stress as well as memory impairments induced by transient cerebral ischemia. GBE has been reported to exhibit anti-inflammatory and neuroprotective properties in other studies ( Liang et al, 2018 ).…”
Section: Discussionsupporting
confidence: 92%
“…Pre-treatment and post-treatment with EGB1212 increased both hippocampal neuron survival and spatial learning and memory functions after global cerebral ischemia/reperfusion in rats (Yin et al 2013). However, Vaghef and Bafandeh Gharamaleki (2017) reported that pretreatment with G. biloba was not as effective as exercise in recovering from memory impairment, although its effect on oxidative stress in the hippocampus was supported. Moreover, GK alleviated neurological impairments and accelerated angiogenesis of the ipsilateral cortex and striatum injured by tMCAO in a mouse model (Chen et al 2018c).…”
Section: Mechanisms Of Ginkgolides and Bilobalide In Neuron Protectiomentioning
confidence: 99%